2012
DOI: 10.1007/s10620-012-2358-2
|View full text |Cite
|
Sign up to set email alerts
|

An Inter-Observer Agreement Study of Autofluorescence Endoscopy in Barrett’s Esophagus Among Expert and Non-Expert Endoscopists

Abstract: The IOA for AF positive lesions is fair to moderate using AFI images which improved with addition of HRE. The overall accuracy of identifying dysplasia was modest, and was better when AFI and HRE images were combined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…In Barrett's esophagus, accuracy for diagnosing dysplasia using AFI was 69 % -76 %, and this was further improved if high resolution white-light endoscopy (WLE) images were also available; interobserver agreement was fair to moderate [48].…”
Section: Autofluorescence Imaging and Optical Diagnosismentioning
confidence: 99%
“…In Barrett's esophagus, accuracy for diagnosing dysplasia using AFI was 69 % -76 %, and this was further improved if high resolution white-light endoscopy (WLE) images were also available; interobserver agreement was fair to moderate [48].…”
Section: Autofluorescence Imaging and Optical Diagnosismentioning
confidence: 99%
“…In a further multicenter randomized trial by Curvers et al, 99 patients with Barrett's esophagus and a confirmed low-grade intraepithelial neoplasia underwent ETMI and SVE. The results show that, despite ETMI detecting 22 more suspect lesions for targeted biopsies, there was no significant difference in the overall histological yield (targeted + random) between ETMI and SVE [13]. The false-positive grading of dysplastic areas by AFI might depend-at least in part-on the observer's experience.…”
Section: Afi In Upper Gi Neoplasiamentioning
confidence: 81%
“…Since dysplastic changes are mainly associated with the epithelial morphology and dysplastic epithelium does not feature any prominent fluorophores, the assumption here is that autofluorescent radiation generated in the submucosa will be attenuated differently when passing through the epithelium, highlighting dysplastic changes. Recent studies demonstrated that while AFI can improve the detection rate of HGD in BE when used by an experienced operator 46 , it also has a relatively high false-positive rate (81%) 47 . Therefore, AFI endoscopy could be useful as a rapid initial evaluation technique to identify suspicious locations in BE, but would require subsequent assessment with another more specific technique for HGD confirmation.…”
Section: Resultsmentioning
confidence: 99%